Incommunicado detention and torture in Spain, Part IV: Psychological and psychiatric consequences of ill-treatment and torture: trauma and human worldviewsi - Hárdi, Lilla; Navarro-Lashayas, Miguel Angel; Pérez-Sales, Pau; Lopez-Neyra, Gabriela; Martínez, Maitane Arnoso; Morentin, Benito (Torture Journal, 2018)
Background: Most literature on psychological consequences of torture is related to prolonged detention. Psychological consequences of intensive physical and psychological torture in brief detention have not been investigated. The aim of this study is to analyse the psychological impact of torture in short-term incommunicado detention. Method: A sample of 45 Basque people who had allegedly been subjected to ill-treatment or torture whilst held in incommunicado detention between two and 11 days in Spain in the period 1980-2012 was analysed. The period between detention and evaluation ranged between two and 12 years. Each case was evaluated by several psychiatrists and psychologists. Clinical interviews which followed the Istanbul Protocol were assessed, as were psychometric tests (Post-traumatic Checklist-Civilian version (PCL-C), Beck Depression Inventory (BDI) and Vital Impact Assessment Questionnaire (VIVO)) and external documentary evidence. A cumulative prevalence of psychiatric diagnosis (ICD-10) from the period of detention was established. Findings. Post-traumatic stress disorder (PTSD) was the most frequent diagnosis (53%). Enduring personality change after a catastrophic experience was detected in 11% of subjects. Other diagnoses were depressive disorders (16%) and anxiety disorders (9%). Psychometric evaluation at the time of the study showed symptoms of PTSD in 52% of the subjects (with a tendency for these symptoms to diminish over time) and depressive symptoms in 56%. The VIVO questionnaire discerned two subgroups of survivors: “affected” survivors (36%); and “resilient” survivors (64%). Interpretation. The data demonstrated two important issues: the undervalued damaging effect of intensive torture in short-term detention and the long-lasting psychological damage of the same over time.